Normative reasons and motivational capacities - Jean Caiaffo Caldas (Filosofia Unisinos, 2024)
A very influential idea on the nature of normative reasons is that the existence of normative reasons for action depends on the motivational capacity of the agents whose reasons they are: there are reasons for an agent to act only if she has the capacity to be moved to act for those reasons. Many theories of reasons developed in recent years imply at least some version of that idea, and many find it attractive since it incorporates some widespread assumptions about the role of reasons. In this paper, I argue that that idea, understood in any of its prominent readings, is ultimately false. First, I endorse the claim that there is at least one case that shows the possibility of the so-called ‘elusive reasons', that is, roughly, reasons whose existence depends on the agent’s ignorance of the facts that constitute them. Then, I argue that all the crucial objections recently elaborated to the possibility of elusive reasons ultimately fail. The upshot is that we should not aim to explain the nature of normative reasons in terms of motivational capacities of the agents whose reasons they are.